Knowledge and practice of neurological assessment using glasgow coma scale among critical care nurses at Hospital Universiti Sains Malaysia - Anuar, Siti Zulaikha Khairul (Universiti Sains Malaysia, 2024)
GCS was a neurological assessment tool utilised to evaluate the degree of consciousness in individuals suffering from brain injury. The study aims to assess knowledge and practice assessment of the Glasgow Coma Scale (GCS) among critical care nurses at Hospital Universiti Sains Malaysia (HUSM). Besides that, this study also investigates the association between knowledge and selected sociodemographic factors (level of education and years of working experience) of GCS among critical care nurses at HUSM. A cross-sectional study design was used in this research. The data was collected using a hard copy questionnaire distributed to the respondents. Data was collected using a self- administered questionnaire. Data collected were statistically analysed using the SPSS software version 27. The study used descriptive statistics and Pearson Chi-square. The findings of the study revealed that 70 (51.1%) of participants have a good level of knowledge GCS and only 33 (24.1%) of participants have a good level of practice assessment GCS. There was no association between sociodemographic factors [level of education (p = 0.221) and years of experience (p = 0.634)] and the level of knowledge GCS. Lastly, there was no association between sociodemographic factors [level of education (p = 0.534) and years of experience (p = 0.942)] and the level of practice assessment GCS. In conclusion, the level of knowledge and practice of GCS among critical care nurses must be enhanced and improved and it should be a more structured and detailed approach to teaching the skill that should go along with demonstrations.